Pengembangan LKPD Berbasis Pendekatan Saintifik untuk Melatih Kemampuan Berpikir Kritis Matematis - Novi Avila Junianti; Isnaniah Isnaniah; M. Imamuddin; Arifmiboy Arifmiboy (Lembaga Pengembangan Kinerja Dosen, 2025)
This study is founded on the issues identified, specifically the dearth of learning resources, the LKPD's lack of training in mathematical critical thinking, and the fact that the LKPD that is currently available was created by educators who did not follow a scientific methodology, which has led to students' low levels of mathematical critical thinking. In order to educate mathematical critical thinking skills in class VIII MTsS Asy-Syarif Koto Laweh for the 2023–2024 academic year, this project intends to produce LKPD based on a scientific approach that satisfies the requirements of validity, practicality, and effectiveness. Using Sugiyono's development paradigm, this study is called research and development, or R&D. Student answer surveys, mathematical critical thinking ability assessments, and validation sheets are the equipment. The techniques for data analysis that are employed are validity analysis, practicality analysis, analysis of effectiveness. Based on development study conducted, LKPD is obtained with a validity level of 84.2%, of which 82.33% are on extremely practical criteria, 78.94% are on effective criteria, and 82.33% are on highly valid criteria for the level of practicality. We may conclude that the LKPD Asy-Syarif Koto Laweh created, which is based on the Scientific Approach to Train Mathematical Critical Thinking Skills in Class VIII MTsS, satisfies the requirements of being valid, practical, and efficient.